Microfluidic flow sensor based on chronoamperometric measurements in a microchannel - Harsh Deswal; Ullas Pandey; Shiv G. Singh; Amit Agrawal (International Journal of Thermofluids, 2024)
Microfluidics explores the fluid behavior at micron scale and is therefore suited to applications that need precise manipulation of fluids at small length or volume scales. In a span of over two decades, microfluidics has become an essential tool for modern genome sequencing platforms, single-cell analysis and common diagnostic tests. Despite many successful applications, the field has various challenges: Fabrication processes are yet to transition to commercial materials, microfluidic systems are reliant on skilled operators, and supporting equipment. Technological innovations in automation are needed to enable easy to use, completely on-chip microfluidic systems. Sensors are a critical component of any automated system. Fluid and flow properties such as flow rate, pressure, temperature, viscosity are critical to applications in drug development, and material/chemical synthesis. The flow rate (μL/min or nL/min) predictions based on external (off-chip) flow measurements can lead to erroneous calculations. The present work explores a technique based on chronoamperometry to measure flow rates inside a microchannel. Chronoamperometry based redox cycling of aqueous NaCl was performed by using interdigitated electrodes (IDE). The sensor measures current transients (which are modulated by the flow rate of the solution) effected by redox reactions on surface of the electrodes. The sensor demonstrated a sensitivity of 0.016 (μL/min)−1 change in charge transfer per unit change in flow rate and 3σ resolution of 9.3 μL/min. The calibration curve is linear in the range 0 – 200 μL/min, with a limit of detection (LoD) of 5 μL/min, making it suitable for various microfluidics applications.